ChemInform Abstract: From Lignin Association to Nano‐/Micro‐Particle Preparation: Extracting Higher Value of Lignin. Issue 50 (November 2016) - Zhao, Wenwen; Simmons, Blake; Singh, Seema; Ragauskas, Arthur; Cheng, Gang
Abstract: Review: 76 refs.